2004
DOI: 10.1158/0008-5472.can-03-2558
|View full text |Cite
|
Sign up to set email alerts
|

Normal Cells Control the Growth of Neighboring Transformed Cells Independent of Gap Junctional Communication and Src Activity

Abstract: The growth of many types of cancer cells can be controlled by surrounding normal cells. However, mechanisms underlying this phenomenon have not been defined. We used a layered culture system to investigate how nontransformed cells suppress the growth of neighboring transformed cells. Direct physical contact between transformed and nontransformed cells was required for growth suppression of transformed cells in this system; communication by diffusible factors was not sufficient. However, significant gap junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 61 publications
8
92
0
Order By: Relevance
“…Working with the same v-src-transformation system, Alexander et al (46) showed that the suppression of transformed cell growth by neighboring nontransformed cells required direct physical contact; communication by diffusible factors was not sufficient. Importantly, the src-kinase activity of the transformed cells was not inhibited by the contact with the nontransformed cells.…”
Section: Intercellular Surveillance (Microenvironmental Control)mentioning
confidence: 99%
“…Working with the same v-src-transformation system, Alexander et al (46) showed that the suppression of transformed cell growth by neighboring nontransformed cells required direct physical contact; communication by diffusible factors was not sufficient. Importantly, the src-kinase activity of the transformed cells was not inhibited by the contact with the nontransformed cells.…”
Section: Intercellular Surveillance (Microenvironmental Control)mentioning
confidence: 99%
“…90,91 Some of these genes encode factors that promote cell migration. For example, Src induces the expression of Slit2.…”
Section: Src and Robo1mentioning
confidence: 99%
“…For example, Src induces the expression of Slit2. 90 Slit2 is a secreted protein that binds to a receptor called "Robo1." 92,93 Robo1 is a transmembrane receptor of the immunoglobulin family.…”
Section: Src and Robo1mentioning
confidence: 99%
See 2 more Smart Citations